2009
DOI: 10.1073/pnas.0902324106
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the EutL shell protein of the ethanolamine ammonia lyase microcompartment

Abstract: Bacterial microcompartments (BMCs) are specialized organelles that use proteinaceous membranes to confine chemical reaction spaces. The ethanolamine ammonialyase microcompartment of Escherichia coli represents such a class of cytosolic organelles that enables bacteria to survive on small organic molecules such as ethanolamine as the sole source for carbon and nitrogen. We present here the crystal structure of the shell protein EutL at 2.2-Å resolution. With 219 residues, it is the largest representative of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 22 publications
(23 reference statements)
2
94
0
Order By: Relevance
“…-GFP and the MCP, a competition experiment was performed. PduP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] -GFP was produced via an isopropyl-β-D-thiogalactopyranoside (IPTG)-inducible promoter in a WT background that also produced PduP. MCPs were purified, and Western blotting was used to detect the PduP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] -GFP and PduP (Fig.…”
Section: A Short Region Of the N Terminus Of Pdup Is Sufficient For Pmentioning
confidence: 99%
See 3 more Smart Citations
“…-GFP and the MCP, a competition experiment was performed. PduP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] -GFP was produced via an isopropyl-β-D-thiogalactopyranoside (IPTG)-inducible promoter in a WT background that also produced PduP. MCPs were purified, and Western blotting was used to detect the PduP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] -GFP and PduP (Fig.…”
Section: A Short Region Of the N Terminus Of Pdup Is Sufficient For Pmentioning
confidence: 99%
“…A similar experiment was performed by producing PduP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] -MBP in place of PduP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] -GFP. Western blots showed that PduP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]…”
Section: A Short Region Of the N Terminus Of Pdup Is Sufficient For Pmentioning
confidence: 99%
See 2 more Smart Citations
“…A second observation for a putative two-state pore in a tandem BMC protein was described for EutL (58,68), in which the open form has a negatively charged pore of 11 Å in diameter, and the relatively closed form has three small perforations (of 2.2 Å diameter at their narrowest point), each formed within a subunit (Figure 3). An additional observation of pores formed within a tandem BMC protein, similar to those in the relatively closed form of EutL, was reported for the newly described Etu BMC (33).…”
Section: Tandem Bmc-domain Containing Proteinsmentioning
confidence: 79%